(untitled) (International Journal of Food and Nutritional Sciences, 2022)
During the Kharif season 2020-2021, an investigation was set up at the Research plot, Department of Agronomy, AKS University, Satna (M.P.) to behold the effect of cultivars and biofertilizers on the growth and yield of green gram. The experiment was designed using a Factorial Randomized Block Design with two factors: varieties and biofertilizers. Four varieties which were tested under investigation were Shikha (V1), Virat (V2), PM-5 (V3) and PDM 139 (V4) and three biofertilizers were Rhizobium (B1), ZSB (B2) and PSB (B3) each @ 20 g/kg seed. Results from the investigation revealed that maximum plant height (67.56 cm), number of leaves per plant (15.80), number of branches per plant (6.16), number of root nodules per plant (17.42), number of pods per plant (19.16), pod length (6.55 cm), number of seeds per pod (9.36), test weight (38.06 g), grain yield (11.02 q/ha) and stover yield (21.84 q/ha) were noted in variety ‘Shikha’. In the case of biofertilizers, inoculation with Rhizobium resulted in significantly better plant height (64.29 cm), number of leaves per plant (14.42), number of branches per plant (4.82), number of root nodules per plant (14.63), number of pods per plant (15.10), pod length (4.70), number of seeds per pod (7.55), test weight (34.61 g), grain yield (8.64 q/ha) and stover yield (18.50 q/ha). Therefore, the variety ‘Shikha’ and inoculation with Rhizobiumcan be adopted to fetch a higher yield of green gram.